Adaptive Voice Intelligence Platform: A Five-Layer Architecture for Self-Learning, Context-Aware Commercial Interactions - Sharma, Vivek (Emerging Frontiers Library for The American Journal of Engineering and Technology, 2025)
This article presents a novel five-layer adaptive voice intelligence platform that transcends the limitations of traditional command-based voice interfaces by implementing a comprehensive architecture for self-learning, context-aware commercial interactions. The proposed system addresses critical gaps in current voice technology through the integration of [Large Language Models] LLM-augmented multi-turn intent parsing, contextual session graph engines, zero-shot voice workflow compilation, reinforcement-tuned optimization, and comprehensive evaluation frameworks. Unlike existing voice assistants that rely on predefined commands and static decision trees, this platform enables natural conversational interactions capable of understanding complex, multi-constraint queries while maintaining persistent memory across sessions and devices. The architecture demonstrates significant improvements in intent recognition accuracy, task completion rates, and user satisfaction across diverse industry deployments, including retail, financial services, healthcare, logistics, and accessibility applications. Through its no-code configuration capabilities and continuous learning mechanisms, the platform democratizes voice interface development while ensuring enterprise-grade security, explainability, and regulatory compliance. This article establishes a transformative framework that elevates voice from a supplementary input method to a primary interface modality, providing a foundation for realizing truly intelligent human-computer interaction that matches and potentially exceeds traditional graphical user interfaces in efficiency, accessibility, and user engagement.